Aerodynamic Design and Performance Analysis of Small Scale Horizontal Axis Wind Turbine with Different Blade Configurations - Mansi, Aktham Sami Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Wind energy has emerged as one of the mostly utilized renewable energy sources in recent years. The use of small-scale horizontal axis wind turbines (HAWT) as a source of electricity is a viable solution. Despite significant progress in the wind energy field, there is always space for improvement in terms of efficiency, cost and the energy extracted. This thesis discusses the aerodynamic design and performance analysis of a small scale HAWT using two reliable methods: The blade element momentum (BEM) method and the computational fluid dynamics (CFD) method. This study is divided into two major parts. Two blade configurations with the same length of 5m are designed and analysed. The first part discusses the aerodynamic performance analysis of the 1st blade configuration using the BEM method. The blade is designed and aerodynamically optimized using QBlade software. Power output, power coefficient, and annual yield for a given Weibull distribution is determined using QBlade software. The second part investigates the impact of integrating a stationary sealed gap trailing edge flap to the 1st blade configuration (2nd configuration) for HAWT applications using both CFD and BEM methods. Accordingly, performance of the 3D blade with a trailing edge flap is determined. Finally, a comparative analysis is conducted to find the optimal blade design amongst both configurations based on power output and annual yield. The BEM results show that At the design tip speed ratio of 7, the power coefficient in the 2nd design configuration is 8.3% higher than the 1st design configuration. According to the 2nd configuration, the CFD method over-predicts the power coefficient compared with the BEM method. The power coefficient from 3D CFD simulation is approximately 12% higher. The annual yield of the wind turbine with the 1st and 2nd configuration is found as 6378 kWh/year and 6944 kWh/year respectively.

ÖZ: Rüzgar enerjisi, son yıllarda en hızlı geli¸sim gösteren yenilenebilir enerji kaynaklarından biri olarak öne çıkmaktadır. Öte yandan, küçük ölçekli yatay eksenli rüzgar türbinlerinin (YART) elektrik üretimi amaçlı kullanımı uygulanabilir bir yöntem olarak görülmektedir. ¸Su ana dek rüzgar enerjisi alanında önemli yenilikler saglanmasına ra ˘ gmen, verimlili ˘ gin arttırılması, maaliyetlerin azaltılması ve enerji ˘ üretim performansının arttırılması anlamında geli¸sime açık yönler bulunmaktadır. Bu çalı¸smada, küçük ölçekli yatay eksenli bir rüzgar türbininin aerodinamik tasarımı ve performans analizleri gerçekle¸stirilmi¸stir. Bu amaçla Kanat Elemanı Momentum (KEM) yöntemi ve Hesaplamalı Akı¸skanlar Dinamigi (HAD) yöntemi olmak üzere ˘ iki farklı etkin teknik kullanılmı¸stır. Çalı¸sma iki farklı temel kısma bölünmü¸stür. ˙Ilgili kısımlarda, 5m uzunluga sahip iki farklı kanat konfigürasyonu tasarlanarak analiz ˘ edilmi¸stir. ˙Ilk bölüm, birinci kanat konfigürasyonun aerodinamik performansının KEM yöntemi kullanılarak incelenmesini kapsamaktadır. ˙Incelenen kanat, QBlade programında tasarlanmı¸s ve aerodinamik olarak optimize edilmi¸stir. QBlade programı kullanılarak, bu kanat konfigürasyonunun sagladı ˘ gı güç çıktısı, güç katsayısı ve seçilmi¸s belirli bir ˘ Weibull dagılımına göre yıllık enerji üretimi belirlenmi¸stir. ˘ Çalı¸smanın ikinci bölümünde, YERT uygulamaları için, birinci kanat konfigürasyonuna, sabit sızdırmaz bo¸sluklu arka kenar kanatçıgının entegre ˘ edilmesinin (ikinci konfigürasyon) etkisi, KEM ve HAD yöntemleri kullanılarak incelenmi¸stir. Bu baglamda, arka kenar kanatçıklı üç boyutlu kanadın performansı ˘ analiz edilmi¸stir. Son olarak, her iki konfigürasyon, güç çıktısı ve yıllık enerji üretimi parametrelerine göre kar¸sıla¸stırmalı olarak incelenmi¸s ve ideal kanat tasarımı belirlenmi¸stir. KEM sonuçlarına göre, kanat ucu hızının 7 oldugu durum için, ikinci kanat ˘ konfigürasyonunun güç katsayısı birinci konfigürasyona göre 8.3% daha yüksek olarak bulunmu¸stur. ˙Ikinci kanat konfigürasyonu için uygulanan iki farklı analiz yöntemi kar¸sıla¸stırıldıgında, HAD yönteminin, güç katsayısını, KEM yöntemine göre ˘ yakla¸sık 12% daha yüksek olarak hesapladıgı görülmü¸stür. Son olarak, birinci ve ˘ ikinci kanat konfigürasyonunu kullanan bir YERT’nin yıllık enerji üretimi, sırasıyla 6378 kWh/yıl ve 6944 kWh/yıl olarak hesaplanmı¸stır.
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2021. Supervisor: Asst. Prof. Dr. Devrim Aydın.
Keywords: Mechanical Engineering Department; Renewable energy sources--Wind Energy--Wind power; Electric power transmission--Electric power transmission; QBlade, Wind Turbine, BEM, CFD, Trailing Edge Flap, Numerical Analysis, Blade Configuratio